The use of an anaerobic incubator for the isolation of anaerobes from clinical samples. Issue 10 (October 1982) - Berry, P L; Taylor, E; Phillips, I
Abstract : An anaerobic incubator was compared with a standard jar system for the isolation of anaerobes from clinical material. Seventy specimens were selected as likely to yield anaerobes: 342 different anaerobes were isolated in the incubator and 347 in anaebrobic jars. These included Bacteroides spp (43%), Peptococcus spp (26%), Peptostreptococcus spp (13%), Veillonella spp (7%), Fusobacterium spp (7%), Clostridium spp (2%) and miscellaneous Gram-positive nonsporing bacilli (2%). Differences in isolation rates for each system were inconsistent and minor. Sixteen anaerobes were chosen for quantitative tests at the beginning and end of the study period. Miles and Misra counts showed a slight advantage of the incubator for F nucleatum, but no difference for B fragilis, B thetaiomicron, B uniformis, B bivius, B corrodens, F mortiferum, Ps anaerobius, P prevotii or Propionibacterium acnes. In almost all cases, colonies in anaerobic jars were slightly larger than those in the incubator. Disc antibiotic sensitivity tests gave the same results in each system, at the beginning and end of the study period. The anaerobic incubator provides an effective means of isolation of anaerobes in a clinical laboratory. However, several design features of the prototype would require change if the system were introduced.